ADAPTATION PECULIARITIES OF HIGHER EDUCATION STUDENTS IN CRISIS CONDITIONS - Pantiuk, Tetiana; Pantiuk, Mykola; Pahuta, Myroslav; Nadimyanova, Tetiana; Myskiv, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Dramatic events related to the Russian-Ukrainian war shook up not only Ukraine, but the entire civilized world. The war exacerbated not only economic, political, and demographic problems, but also defined as priority tasks the physical rescue of a person, the preservation of his life and health, comprehensive assistance in migration, arranging life and living in critical conditions, overcoming fear and hopelessness. Russia broke all the rules of life on the planet and distinguished itself by atrocities, murders of civilians, looting, and rape. Ukrainians, who are faced with the challenges of life and death today, are looking for ways to preserve not only their territories, above all, their language, culture, education, and authenticity. Our desire for global and European values requires not only the support of the Armed Forces, but each person in his place to work to the best of his ability to support public life in all its dimensions. Education also requires new approaches to content, values, psychological and pedagogical principles, organizational forms, and tools to overcome the challenges facing Ukraine today. In the center of attention of the higher school now is the student whose life, in addition to traditional challenges, has been complicated by war, uncertainty about the future, confusion, despair, a difficult economic situation, the lack of an opportunity to provide basic needs, distance learning, etc. All this, as evidenced by our survey of students of higher education, often leads to maladaptation, depressive states, disappointment, apathy, anxiety, etc. Therefore, the stated situation actualizes the problem of finding optimal ways of adaptation of higher education students in crisis conditions, which will be outlined in our research. In order to identify the peculiarities of students` adaptation to crisis conditions, we conducted a study related to various aspects of their life. It included the possibility to receive psychological support during a crisis period. It is associated with a pandemic and war; awareness and understanding of external and internal factors of crisis conditions that influence student life; the process of adaptation to distance learning in crisis conditions; elucidation of the reasons  that negatively  influence/influenced the distance learning process in crisis conditions; determining positive  potential of distance learning in crisis conditions; evaluation by  students of educational process effectiveness in crisis conditions.